INTERPRETATION BY AMIRA MUIZZI FROM UNSURI BALKHI (Scientific journal of the Fergana State University, 2024)
The article talks about Unsuri Balkhi, one of the outstanding figures of Tajik-Persian poetry, as well as the works of Amir Muizzi, who made a significant contribution in this context. From the thoughts of famous researchers of the East and West Muhammad Awfi, Zabihullah Safo, Shafei Kadkani, Edward Brown, Furuzonfar, Bertels and others, these issues were analyzed.